Advanced Feature Matching Approach for Object Detection in Video - Kaur, Ramanpreet; Sodhi, Gurinder (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Detection of object from a video and then tracking ofthat object is an important task in computer vision. Objectdetection means to detect or locate objects from consecutiveframes of a video file. On the other hand, tracking is a process oflocating moving multiple interested objects in a video file or camera depends upon the requirement. In technical term, object tracking defined as the route or path of an interested or required object in the frame plane which is moving around the image plane. It has the becoming the most emerging technology ofnowadays due to the computational power, good quality and low cost video camera. aditionally various techniques were used for the motion detection as the feature extraction is the crucial part of the detection process. But each technique used has somelimitations due to which they were not able to detect the small variation in the features. In this work the LBP technique is used for the detection and matching of the features from the frame of the video. This technique is considered to be better technique for the feature extraction. From the results obtained it is concluded that this technique of detection of feature is better and efficient than the traditional technique.